2010
DOI: 10.1111/j.1365-2648.2010.05376.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ work environments, care rationing, job outcomes, and quality of care on neonatal units

Abstract: Additional research on the determinants of nurse outcomes, the quality of patient care, and the impact of rationing of nursing care on patient outcomes in neonatal intensive care units is required. The Neonatal Extent of Work Rationing Instrument appears to be a useful tool for monitoring the extent of rationing of nursing care in neonatal units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
214
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(230 citation statements)
references
References 41 publications
10
214
0
6
Order By: Relevance
“…1 Medical professionals in the critical care setting are at risk for burnout, 2,3 fueled by frequent changes in technology and guidelines, endeavors for high-quality care, and emotional challenges of dealing with critical ill patients and their families. [4][5][6] Burnout affects 25% to 50% of NICU providers, 1,5 with up to one-half of nurses and physicians meeting criteria for severe burnout in all specialties. 7 -10 Burnout among health care providers has been linked to adverse patient events in multiple settings, including increased rates of health care-associated infections 11,12 and self-reported errors.…”
Section: What This Study Addsmentioning
confidence: 99%
“…1 Medical professionals in the critical care setting are at risk for burnout, 2,3 fueled by frequent changes in technology and guidelines, endeavors for high-quality care, and emotional challenges of dealing with critical ill patients and their families. [4][5][6] Burnout affects 25% to 50% of NICU providers, 1,5 with up to one-half of nurses and physicians meeting criteria for severe burnout in all specialties. 7 -10 Burnout among health care providers has been linked to adverse patient events in multiple settings, including increased rates of health care-associated infections 11,12 and self-reported errors.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Studies exploring missed care under the implicit rationing approach have found that nursing activities related to surveillance are among the top five most frequently left undone (Jones et al., 2015; Rochefort & Clarke, 2010; Schubert et al., 2012). These findings resonate with analysis by Smith (2010) about the acute problem regarding frequency of physiological observations.…”
Section: Introductionmentioning
confidence: 99%
“…The national and international literature has made consistent recommendations, especially to hospital institutions, regarding the work environment, and emphasize that nurses and effective care contribute to the process of patient recovery (2)(3) . Other studies stress that in environments favorable to the professional practice, patient safety and quality of care are improveds (4)(5) , which contributes to promote an safety climate (6) , reducing the occurrence of adverse events (7) . In this context, the environment of health organizations is a determining factor in the quality and safety of health care, and the nursing team provides a significant contribution to the creation of a safety environment for health.…”
Section: Introductionmentioning
confidence: 99%